OVERCOMING OVERLOAD OF DISTRIBUTION TRANSFORMERS WITH THE UPRATING METHOD AT THE SM01 TIE LINE SINABANG ULP SINABANG - Newmont Djoel Panggabean; Hamdani; Adisastra Pengalaman Tarigan (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study discusses the overcoming overload problem in the distribution transformer that occurred at the SM01 Tie Line Sinabang ULP Sinabang Feeder. Transformer overload can lead to decreased electrical system performance, equipment damage, and potential power outages. The method used in this study is uprating, which is increasing the capacity of the transformer to meet the increasing load needs. The study begins with the analysis of historical load data and the identification of the factors that cause overload. Furthermore, simulations were carried out to evaluate the performance of the transformer under different load conditions. The uprating method is applied by taking into account the applicable technical specifications and operational standards. The simulation results show that increasing the capacity of the transformer can reduce the frequency of overload events and improve the reliability of the power supply. From the results of the study, it was concluded that the uprating method was effective in handling the problem of overload of distribution transformers at SM01 Feeder. Recommendations for the implementation of uprating and periodic monitoring of transformer conditions are also prepared to ensure operational continuity and safety of the electricity distribution system.